2009
DOI: 10.1016/j.neulet.2009.03.064
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticle–chelator conjugates as inhibitors of amyloid-β aggregation and neurotoxicity: A novel therapeutic approach for Alzheimer disease

Abstract: Oxidative stress and amyloid-β are considered major etiological and pathological factors in the initiation and promotion of neurodegeneration in Alzheimer disease (AD). Insomuch as causes of such oxidative stress, transition metals, such as iron and copper, which are found in high concentrations in the brains of AD patients and accumulate specifically in the pathological lesions, are viewed as key contributors to the altered redox state. Likewise, the aggregation and toxicity of amyloid-β is dependent upon tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
67
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(68 citation statements)
references
References 54 publications
(58 reference statements)
0
67
0
1
Order By: Relevance
“…24 Suspeita-se que a secreção e a deposição do βA, bem como a agregação das placas senis ocorrem num segundo plano, funcionando como uma tentativa das células se protegerem contra os danos provocados pelo stress oxidativo. 25 Biometais como o cobre (Cu) e o zinco (Zn) circulam no cére-bro de forma regulada, através da barreira hematoencefálica. O Cu encontra-se distribuído por todo o organismo preferencialmente na forma de complexo orgânico, normalmente associado a metaloproteínas com função enzimática.…”
Section: Importância Dos Metais Em Doenças Neurodegenerativasunclassified
“…24 Suspeita-se que a secreção e a deposição do βA, bem como a agregação das placas senis ocorrem num segundo plano, funcionando como uma tentativa das células se protegerem contra os danos provocados pelo stress oxidativo. 25 Biometais como o cobre (Cu) e o zinco (Zn) circulam no cére-bro de forma regulada, através da barreira hematoencefálica. O Cu encontra-se distribuído por todo o organismo preferencialmente na forma de complexo orgânico, normalmente associado a metaloproteínas com função enzimática.…”
Section: Importância Dos Metais Em Doenças Neurodegenerativasunclassified
“…Another approach may be to conjugate chelators to nanoparticles that can cross the blood-brain barrier to chelate metal ions, and then exit to remove them (261)(262)(263). Recently, Nano-N2PY, a prototype nanoparticle-chelator conjugate was demonstrated to inhibit AβPP-Aβ aggregation and reduce AβPP-Aβ-associated cortical neuron toxicity in vivo (264). Another novel approach involved the development of site-activated multifunctional chelators, such as HLA20A, that become activated by binding and inhibiting acetylcholinesterase, resulting in the release of an active chelator that reduces AβPP-Aβ fibrillization and oxidative stress (265,266).…”
Section: Radical Scavengers-epidemiological Studies Suggested That Lomentioning
confidence: 99%
“…Later, Liu et al suggested another synthesized nanoparticle-chelator conjugate (named Nano-N2PY), and demonstrated its in vitro ability to inhibit the cytotoxic effects of Aβ on human cortical neurons [81]. The nanoparticles used in this study were made of carboxyl functionalized polystyrene.…”
Section: Iron Chelatorsmentioning
confidence: 99%
“…In addition, such a nanoparticle conjugate is capable of transporting metal chelators across the BBB, without disrupting the metal binding feature of the chelator. In addition to increasing the efficacy of metal chelating strategy, these nanoparticle conjugates were shown to reduce the toxicity of chelation strategy, by decreasing the lipophilicity of the chelators [81].…”
Section: Iron Chelatorsmentioning
confidence: 99%